Bompa's insect expedition - Suzuki, David, 1936-; Kyi, Tanya Lloyd, 1973- (David Suzuki Institute ; Greystone Kids, 2023)
"Let's go on an insect expedition for kids ages 4 to 8! This adventure into the extraordinary world of bugs is inspired by David Suzuki's adventures with his own grandkids. It's time for the twins to go on a nature expedition with Bompa. What marvelous place will they explore this time? Tidepools at the sea? The pond full of frogs' eggs? Maybe deep in the forest? But to their disappointment, they are just exploring outside the door. Yet, as they begin to search for insects, they find world-champion flyers, eaters, and weightlifters. And more tiny surprises at every turn! With their Bompa at their side, they find a way to recognize the amazing feats and important role of all insects. . . even the annoying ones! Featuring gorgeous art by Qin Leng, this picture book is a lush, colorful tour through a world we too often overlook. This exciting and educational tribute to bugs features: - Amazing facts about insects, including backmatter pages - Information on how kids can help bugs thrive - A celebration of grandparents: depicts the fun two children have with their grandfather After reading Bompa's Insect Expedition, kids will come away understanding how essential bugs are to our world."--